SSRI use during pregnancy and risk for postpartum haemorrhage: a national register‐based cohort study in Sweden. (1st April 2020) - Skalkidou, A; Sundström‐Poromaa, I; Wikman, A; Hesselman, S; Wikström, AK; Elenis, E
Abstract : Objective: Evaluate whether selective serotonin reuptake inhibitor (SSRI) use during pregnancy, as well as prior or current untreated psychiatric illness is associated with postpartum haemorrhage (PPH). Design: National register‐based cohort study based on data from the Swedish Pregnancy Register. Setting: Sweden, nationwide coverage. Population: A total of 31 159 pregnant women with singleton deliveries after gestational week 22 +0 between January 2013 and July 2017. Methods: Pregnant women with self‐reported SSRI use at any time point during pregnancy were compared with non‐SSRI‐treated women with prior or current psychiatric illness, as well as wiith healthy women with no psychiatric illness or reporting SSRI use. Main outcome measures: Postpartum haemorrhage defined as blood loss >1000 ml during the first 2 hours postpartum reported by the delivering midwife or obstetrician. Results: Postpartum haemorrhage prevalence was 7.0% among healthy women, 7.6% among women with prior or current psychiatric illness and 9.1% among women treated with SSRI. The unadjusted odds for PPH among women with prior or current psychiatric illness and women on SSRI treatment were increased by 9 and 34%, respectively, compared with healthy unmedicated women without a history of psychiatric illness (odds ratio [OR] 1.09, 95% CI 1.04–1.14 and OR 1.34, 95% CI 1.24–1.44, respectively). The estimates remained unchanged after adjustment for several confounders (such as maternal age, body mass index [BMI], parity, prior caesarean section, smoking, occupation and country of birth) and potential covariates (such as delivery mode, polyhydramnion, preterm delivery, labour dystocia and infant birthweight >4000 g). Conclusions: Higher risk for PPH was observed both among women treated with SSRI during pregnancy and among women with prior or current psychiatric illness. Tweetable abstract: SSRI use at any point during pregnancy and prior or current history of psychiatric illness was associated with an increased likelihood for PPH. Tweetable abstract: SSRI use at any point during pregnancy and prior or current history of psychiatric illness was associated with an increased likelihood for PPH.